2013
DOI: 10.1097/fbp.0000000000000007
|View full text |Cite
|
Sign up to set email alerts
|

The antinociceptive effects of intracerebroventricular administration of Chicago sky blue 6B, a vesicular glutamate transporter inhibitor

Abstract: Accumulating evidence suggests that vesicular glutamate transporters (VGLUTs), which control the storage and release of glutamate, may play a role in pain processing. Chicago sky blue 6B (CSB6B), which is structurally related to glutamate, is a competitive VGLUT inhibitor without affecting plasma membrane transporters. The present study was designed to investigate the antinociceptive effects of CSB6B in a number of pain models. The hot-plate test was used as an acute thermal pain test. Inflammatory pain was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“… 27 , 28 Finally, Chicago Sky Blue 6B (CSB6B) selectively inhibited the function of VGLUTs and was reported to weaken inflammatory pain in related mouse model. 29 , 30 In this study, the results showed that when miR-190a-5p was upregulated, SLC17A6 was downregulated, IL-1β and IL-6 were decreased in lumbar spinal dorsal horn, and painful behavior was improved. In addition, when SLC17A6 was inhibited, IL-1β and IL-6 were also decreased in lumbar spinal dorsal horn, and pain behavior was also improved.…”
Section: Discussionmentioning
confidence: 62%
“… 27 , 28 Finally, Chicago Sky Blue 6B (CSB6B) selectively inhibited the function of VGLUTs and was reported to weaken inflammatory pain in related mouse model. 29 , 30 In this study, the results showed that when miR-190a-5p was upregulated, SLC17A6 was downregulated, IL-1β and IL-6 were decreased in lumbar spinal dorsal horn, and painful behavior was improved. In addition, when SLC17A6 was inhibited, IL-1β and IL-6 were also decreased in lumbar spinal dorsal horn, and pain behavior was also improved.…”
Section: Discussionmentioning
confidence: 62%
“…The antinociceptive effects of incarvillateine were initially assessed using the acetic acid-induced writhing test as described previously 46 . Briefly, mice were i.p.…”
Section: Methodsmentioning
confidence: 99%
“…The hot plate test was performed as described previously 46 . Mice were individually placed on the surface of a hot plate (HUGO SACHS Elektronik-Harvard Apparatus GmbH, March-Hugstetten, Germany) maintained at 55 ± 0.5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…We validated these results using a different echocardiography system (Supplemental Figure 1, A and B). Previous studies showed that CSB has several biological effects (37,(42)(43)(44)(45)(46). Therefore, we examined the mice for adverse side effects at the end of the in vivo experiment, 21 days after MI.…”
Section: Resultsmentioning
confidence: 99%
“…CSB was shown to have several biological targets, including VGLUT (46), MIF (38), CaMKP (62), RAD51 (39), ubiquitin (40), and the Prion protein (63). In vivo, CSB was shown to attenuate methamphetamine-induced hyperac- tivity (46), to have antinociceptive effects (44), to attenuate secondary injuries in the spinal cord (45), and to modulate feeding in broilers (42).…”
Section: Discussionmentioning
confidence: 99%